Analysis of the Inluence of Human Resource Quality Development, Managerial Coaching, Work Stres, Motivation and Innovation on Business Performance of Micro, Small and Medium Enterprises (MSMEs) in Central Java Province - Indah Ristiyani; Qristin Violinda; Bayu Kurniawan (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Abstract This research aims to determine and analyze the influence of human resource quality development, managerial coaching, work stress, motivation and innovation on MSME business performance in Central Java Province. This study uses a quantitative approach. The population in this research is business actors in Central Java Province, totaling 183,181 micro, small and medium business owners in 2023 in the first quarter with a sample of 399 business owners. The sampling technique used is a probability sampling technique with a simple random sampling method. In collecting data, this research used a Likert scale with 5 assessment criteria for 42 questions. The data analysis technique used is multiple linear regression analysis. The results of this research show that the human resource quality development variable has a positive and significant effect on business performance with a contribution of 13.9%. Managerial coaching has a positive and significant effect on business performance with a contribution of 14.5%. Work stress has a positive and significant effect on business performance with a contribution of 21%. Motivation has a positive and significant effect with a contribution of 8.9%. Innovation has a negative and insignificant effect on business performance with a percentage of 15.1%. Meanwhile, developing the quality of human resources, managerial coaching, work stress, motivation and innovation simultaneously influence the business performance of MSMEs in Central Java Province by 73.4% and the remaining 26.6 is influenced by other variables which are not included in this research. Keywords: Human Resource Quality Development, Managerial Coaching, Job Stress, Motivation and Innovation.